Evaluation of sorghum stover based diets in cattle, sheep and goats - PAILAN, G H; MAHANTA, S K; VERMA, N C (The Indian Journal of Animal Sciences, 2011)
An experiment was conducted to study the nutrient utilization from sorghum stover based diets in cattle, sheep and goat. DM, TDN and DCP intake per kg metabolic body size was higher in cattle than that in sheep and goats. Digestibility of DM, OM, EE, CF, NFE, NDF and ADF was similar in all the species; however, CP digestibility was higher in cattle in comparison to sheep and goats. N retention (as% of intake N) was higher in cattle and sheep than in goats. The TDN and DCP contents of the diets were higher in cattle than in sheep and goats. The experimental results revealed that the nitrogen utilization was poor in goats fed sorghum stover based diets in comparison to cattle and sheep; however, this roughage source can be used as maintenance diets along with supplementation of concentrate mixture (1% of body weight) in cattle, sheep and goats.Â